Shrimadvagbatgeeta: Elixir of Mental and Physical Health/শ্রীমদ্ভগবদ্গীতা : এক অনন্ত জীবন সুধার উৎস (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Shrimadvagbatgeeta, the dialogue between Lord Krishna and Arjuna, has critically been hailed as a treatise on philosophy and Indian ethics. However, the text manifests an exploration of human management in which Lord Krishna appears as a mentor to Arjuna, who was in a state of confusion and dilemma. The dilemma of Arjuna is moral and ethical as it involves dimensions of relationship with kins. Lord Krishna, in his deliberations on duties, consistency, accomplishments of the tasks assigned and selfless actions impart not only motivation and zeal to Arjuna to overcome the dilemma and procrastination, but also guides him to emancipation via selfless devotion.          The purpose of the paper is to explore the psychoanalytic subtext embedded in Shrimadvagbatgeeta by reviewing the sermons of Lord Krishna to Arjuna.
Keywords: Shrimad Bhagwat Geeta; Monu Sanhita; uponishad; karmayog; food habits; Sttaprajna